Qaraqorum in Yuan - Rossabi, Morris (Acta Mongolica, 2022)
The Mongols’ establishment of a capital in the thirteenth century indicated their desire not only to plunder but to rule the domains they had conquered. The placement of the capital in Qaraqorum, in their own native land, appears to have been optimal, and merchants and craftsmen flocked to the city to ply their wares. As Qaraqorum flourished and the population increased, a major flaw became apparent: its hinterland could not fulfill its needs, and in 1267, Qubilai Khan moved the capital to Dadu, which had nearby supplies. Yet Qaraqorum was not abandoned, as it signified the Mongols’ attachment to their own land. In the early fourteenth century, the Yuan dynasty court sought to protect and incorporate it as part of the provincial system. However, the city was unable to govern and tax mobile herders and thus to secure the essential revenue for its needs. It faced considerable difficulties, and the Yuan dynasty itself declined due to internecine struggle, natural disasters, and corruption among Mongol princes. Rebellions erupted, and the founders of the Ming dynasty forced the Yuan court to withdraw from China and to retreat to Qaraqorum. Conflicts between the Ming and the so-called Northern Yuan court finally resulted in the destruction of Qaraqorum in 1388. Yet it retained its appeal and aura for the Mongols and led them to establish their first Buddhist monastery around the site in the sixteenth century.